Augmented telomerase activity and reduced telomere length in parthenium‐induced contact dermatitis. (5th September 2012) - Akhtar, N.; Anand, V.; Verma, K.K.; Sharma, A.
Abstract: Background Parthenium dermatitis is a common chronic inflammatory disease with activated T lymphocytes that recognize the antigens, which leads to proliferation and differentiation. Telomeres and telomerase play an important role in the regulation of life span of the cell. Telomere length maintained by telomerase, are specialized repeats present at the end of chromosomes which protect it from degradation, end‐to‐end fusion and are important for integrity of chromosomes. Objectives The aim of this study was to measure telomerase activity and telomere length in Peripheral blood mononuclear cell (PBMC), CD4 + and CD8 + T lymphocytes from parthenium dermatitis patients. Methods The study includes 50 patients of parthenium dermatitis confirmed by patch testing and 50 healthy controls. Telomerase activity was measured using the telomere repeat amplification protocol using PCR–ELISA kit. Telomere length was measured by using T elo TAGGG Telomere Length Assay Kit. Results Significantly elevated levels of telomerase activity was observed in PBMC, CD4 + and CD8 + T cells of parthenium dermatitis patients as compared with healthy controls. However, significantly reduced telomere length in PBMC, CD4 + and CD8 + T cells have been found in patients than healthy subjects, but there was no difference between CD4 + and CD8 + T cells in patients. Conclusion This study might have provided insight into the role of telomerase in parthenium dermatitis that is characterized by the recruitment of T lymphocytes, which play an important role in this inflammatory disease. The augmented telomerase activity and reduced terminal restriction fragment length might be explored as a potential diagnostic/prognostic marker for parthenium dermatitis in future.